Carrier statistics and ballistic conductance model of bilayer graphene nonoribbon in bgn field effect transistor - Sadeghi, Hatef (2010)
Bilayer Graphene Nanoribbons (BGNs) Carrier statistics and Ballistic conductance in the non-degenerate and the degenerate limits are presented. By definition, two dimensional BGN through AB configuration with width less than De- Broglie wave length is a one dimensional (ID) device. Based on the ID behavior, analytical numerical model of BGNs carrier concentration in the degeneracy limit is obtained. The proposed model has shown that for BGN, carrier concentration on low carrier regime has an exponential relationship with normalized Fermi energy. However from zero to 3knT distance from the conduction or valence bands (for degenerate regime) and at higher carrier concentration, the value of carrier concentration is very sensitive to an increase in normalized Fermi energy which is independent of temperature. Mathematical model and numerical solution of BGNs ballistic conductance is introduced in the degenerate and non-degenerate regimes. At the neutrality point, the behavior of the ballistic conductance for non-degenerate regime corresponds closely to that of the model introduced. Outside the neutrality point, the behavior of the ballistic conductance of the model can be estimated from the degenerate regime approximation. The model confirms that BGN conductance is temperature dependent near the neutrality point and minimum conductance increases with temperature. Beyond the neutrality point, conductance is independent of temperature. The proposed model showed good agreement with experimental data. Since a Bilayer Graphene Nanoribbon Field Effect Transistor (BGNFET) can be shaped by using graphene bilayers with an external controllable voltage which is perpendicular to the layers, its application as a future field effect transistor channel is expected to be widespread.